Relation and Interactions Among Reading Fluency and Competence for Adult Education Learners. Issue 2 (15th May 2013) - Mellard, Daryl F.; Fall, Emily E.; Woods, Kari L.
<x xml:space="preserve">Abstract</x> Statistical analyses of data from an academically diverse sample of 276 adult basic and secondary education learners extends understanding of the relation of and interactions between oral reading fluency and reading competence indices. Significant interactions between total word rate and word error rate that differed in relation to two measures of reading competence suggest that adult literacy instructors should emphasize fluency instruction to a greater or lesser degree depending on whether the major goal of instruction is academic reading (e.g., being able to comprehend a textbook) or functional reading (e.g., being able to fill out a job application).